2019
DOI: 10.1080/00909882.2019.1706098
|View full text |Cite
|
Sign up to set email alerts
|

Communicating resilience: predictors and outcomes of dyadic communication resilience processes among both cancer patients and cancer partners

Abstract: The communication theory of resilience describes five communication processes that serve to promote resilience. This research examines predictors and outcomes of the five resilience processes. This study examines pathways between communication efficacy and relational quality to dyadic communicative resilience processes and from these processes to outcomes of health management and evaluations of dyadic coping. Participants (N = 584) include cancer patients (n = 312) and partners of cancer patients (n = 272). St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…In other words, much of the current literature linking humor to coping conceptualizes humor as a personal resiliency tool that individuals utilize to cope with stressful or traumatic events (Kuiper, 2012), focusing less on the dyadic nature of humor. In a recent examination of humor as an alternative logic, humor positively predicted cancer patient's reports of dyadic coping (Venetis et al, 2020). Findings from the current study further support the relationship between couples' use of humor as a communicative resilience process and dyadic coping efforts.…”
Section: Mechanisms Of Effectsupporting
confidence: 75%
See 2 more Smart Citations
“…In other words, much of the current literature linking humor to coping conceptualizes humor as a personal resiliency tool that individuals utilize to cope with stressful or traumatic events (Kuiper, 2012), focusing less on the dyadic nature of humor. In a recent examination of humor as an alternative logic, humor positively predicted cancer patient's reports of dyadic coping (Venetis et al, 2020). Findings from the current study further support the relationship between couples' use of humor as a communicative resilience process and dyadic coping efforts.…”
Section: Mechanisms Of Effectsupporting
confidence: 75%
“…Maintaining and using communication networks, hereafter communication networks, occurs when individuals engage in communication efforts with those in their social network to alleviate stress associated with a disruption. Communication networks includes talk with one's partner, as evidenced in couples managing a cancer event (Venetis et al, 2020), as well as individuals outside of the dyad who may provide support (Dorrance Hall, 2018). Next, affirming identity anchors, hereafter identity anchors, represents communicative efforts to enhance or reinforce salient identities or values.…”
Section: Communication Theory Of Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Communication that requires effort is more highly valued and respected (Vorys, 1946; Evans and Hayden, 2017). A survey of congressional staff members found that they considered personal letters more influential than personal emails , which outrank personal phone calls .…”
Section: Constituent Communication and Representationmentioning
confidence: 99%
“…Centiment relies upon a diverse panel of participants who are periodically sent surveys on varied topics. Centiment has been used by scholars in a wide array of fields (see, for example, Venetis, Chernichky‐Karcher, and Lillie, 2020; Scaptura and Boyle, 2019; Locke, 2019) because of the diversity and quality of their respondent pool. Centiment also uses screening questions embedded in the survey to ensure that respondents are attending to the questions being asked and not merely clicking on answers.…”
Section: The Mismatch Effectmentioning
confidence: 99%